Pattern of ENT foreign bodies at Lumbini Zonal Hospital, a regional level ENT referral centre in Western Nepal - Pantha, Sandesh; Sharma, B (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Aim: Foreign bodies in ENT account for a significant number of visits to an ENT clinic. Our study was aimed to determinethe load of foreign bodies in an ENT referral centre in western Nepal.Methods: It is a retrospective analysis of all the patients who presented with foreign bodies in the ENT department ofthe Lumbini Zonal Hospital over a period of 9 months from April-December 2009. Charts and outpatient register of theENT department were retrospectively analyzed using SPSS 14.0.Results: Foreign bodies were predominant in the paediatric age group. Aural foreign bodies were the most commonfollowed by nasal foreign bodies. Nonliving foreign bodies were more common than living foreign bodies.Conclusion: ENT foreign bodies can be removed safely in the outpatient clinic without much complication except for theforeign bodies in the oesophagus which require removal under general anaesthesia.